Maltrato infantil y su influencia en el rendimiento académico de los niños y niñas de 4 y 5 años de las instituciones educativas iniciales del distrito de Nueva Cajamarca año 2009 - Pajuelo Alcantara, Inés Hortencia (2010)
The present investigative work consisted on the tapie of the infantile abuse and its influence in the academic yield, for that which one worked with a sample of 85 children of 4 and 5 years of the lnitial level of the lnstitutions Educational lnitials of the district of New Cajamarca. The problem arose due to the experience acquired in our environment and during the development of our professional practicas where different types of abuses were observed that the leaming of the children and girls affect resulting in a low academic yield. For the rising thing next will explain that it is the infantile abuse, types and . consequences. The lnfantile Abuse is any produced physical or psychological damage in a non accidental way causad by its relativas or people of its environment that it happens as a result of physical, psychological, sexual actions, verbal for negligence or action abandonment or omission and that they threatened the normal development so much physical as psychological and emotional of the boy. This problem is defined inside the boys psychological and emotional supposition in relation to its process teaching - leaming, especially in its academic yield. The most common types of infantile abuse found in the investigation are the following ones: 11 1 mistreat physical: lt is any non accidental action on the part of the parents or tutors that it causes physical damage or illness in the boy or it places him in serious risk of suffering it. As they are: Moretones, bums, fractures, bites. 11 1 mistreat Psychological: lt is the hostility verbal chronicle in form of insults, scorn, critic or he/she threatens of abandonment and constant blockade of the infantile interaction initiatives that he/she results in it anguishes, anxiety, distrust, disorder of identity; on the part of any member of the family group. 11 1 mistreat Sexual: lt is any kinds of sexual pleasure with a boy on the part of an adult. The boy can be used for the realization of sexual acts or like object of sexual stimulation.